Suboptimal bone status for adolescents with low motor competence and developmental coordination disorder—It's sex specific. (January 2019) - Chivers, Paola; Rantalainen, Timo; McIntyre, Fleur; Hands, Beth; Weeks, Benjamin; Beck, Belinda; Nimphius, Sophia; Hart, Nicolas; Siafarikas, Aris
Highlights: Bone health differences vary between boys and girls with LMC/DCD. Boys with LMC/DCD had less robust bones than healthy age-matched Australian boys. Girls with LMC/DCD had similar bone health to healthy age-matched Australian girls. Abstract: Background: Australian adolescents with low motor competence (LMC) have higher fracture rates and poorer bone health compared to European normative data, but currently no normative data exists for Australians. Aims: To examine whether there were bone health differences in Australian adolescents with LMC or Developmental Coordination Disorder (DCD) when compared to typically developing age-matched Australian adolescents. Methods and Procedures: Australian adolescents aged 12–18 years with LMC/DCD (n = 39; male = 27; female = 12) and an Australian comparison sample (n = 188; boys = 101; girls = 87) undertook radial and tibial peripheral Quantitative Computed Tomography (pQCT) scans. Stress Strain Index (SSI (mm 3 )), Total Bone Area (TBA (mm 2 )), Muscle Density (MuD [mgcm 3 ]), Muscle Area (MuA [cm 2 ]), Subcutaneous Fat Area (ScFA [cm 2 ]), Cortical Density (CoD [mgcm 3 ]), Cortical Area (CoD [mm 2 ]), cortical concentric ring volumetric densities, Functional Muscle Bone Unit Index (FMBU: (SSI/bone length)) and Robustness Index (SSI/bone length^3), group and sex differences were examined. Outcome and Results: The main finding was a significant sex-x-group interaction for Tibial FMBU (p = .021), Radial MuD (p = .036), and radial ScFA (p = .002). Boys with LMC/DCD had lower tibial FMBU scores, radial MuD and higher ScFA than the typically developing age-matched sample. Conclusion and Implications: Comparisons of bone measures with Australian comparative data are similar to European findings however sex differences were found in the present study. Australian adolescent boys with LMC/DCD had less robust bones compared to their well-coordinated Australian peers, whereas there were no differences between groups for girls. These differences may be due to lower levels of habitual weight–bearing physical activity, which may be more distinct in adolescent boys with LMC/DCD compared to girls.